Teacher Talk Analysis in Classroom Interaction through Flander’s FIACS Technique - Nafisah, Bq Zuhrotun; Setianingsih, Tri (LP2M STIT Palapa Nusantara, 2024)
This research attempts to investigate the teacher talk types employed in classroom interaction using Flander Interaction Analysis Categories System (FIACS) framework. This research was qualitative research with a descriptive method. The research participants were an English teacher and eleventh-grader students of SMAN 1 Gunungsari. The data collection method is audio recording and observation. The data were collected through two class meetings. To analyze the data, the researchers used interaction analysis systems adapted from Flanders (1970). The study’s findings showed that the seven types of teacher talk were found in classroom interaction with varied percentages of certain occurrences. Of the seven types, lecturing and giving directions were mostly applied by the teacher, which indicated that the teacher’s domination in classroom interaction was high. The teacher offered the students more information and knowledge as well as gave them directions, commands, or orders in the learning process. It also showed that the percentage of direct talk was higher than indirect talk. It is expected that the teachers would use this study as a reference to think about the types of teacher talk they should use to raise their students' engagement in classroom interaction.